2021
DOI: 10.3390/galaxies9040075
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Test Particles and Twin Peaks QPOs around Regular Black Holes in Modified Gravity

Abstract: In this work, we have presented a detailed analysis of the event horizon of regular black holes (BHs) in modified gravity known as MOG, the so-called regular MOG BH. The motion of neutral particles around the BH has also been explored. The test particle motion study shows that the positive (negative) values of the MOG parameter mimic the spin of a rotating Kerr BH, providing the same values for the innermost stable pro-grade (retrograde) orbits of the particles in the range of the spin parameter a/M∈(−0.4125,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…Studies of the QPOs can be one of the observational ways to measure the inner edge of an accretion disk around such central compact objects. Recent theoretical models and analyses of observational studies have shown that the orbits where the QPOs are generated, close to the ISCO of the particles [30,59,60]. In other words, the QPO phenomena can play a powerful tool that may allow estimating (approximate) values of the radii of innermost regions of accretion disks and their masses (and radius), and spin of the central compact objects.…”
Section: Qpo Models In Nc Gravitymentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of the QPOs can be one of the observational ways to measure the inner edge of an accretion disk around such central compact objects. Recent theoretical models and analyses of observational studies have shown that the orbits where the QPOs are generated, close to the ISCO of the particles [30,59,60]. In other words, the QPO phenomena can play a powerful tool that may allow estimating (approximate) values of the radii of innermost regions of accretion disks and their masses (and radius), and spin of the central compact objects.…”
Section: Qpo Models In Nc Gravitymentioning
confidence: 99%
“…Here the total mass of the BH is taken, as a test value, to be M = 10M . around the BH, such as QPOs [32,60,66]. In such cases, it is quite complicated to distinguish the central BH type.…”
Section: Qpo Models In Nc Gravitymentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, astrophysical black holes can be mainly observed by the radiation luminosity of the accretion disk, in particular by quasiperiodic oscillation (QPO) frequencies with the ratio 3:2 [6,7]. Using QPOs it is possible to obtain information about spacetime around the black holes and constraints on their total mass, charge, and spin parameters estimated, e.g., in [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The internal magnetic fields are crucial due to the magneto-rotational instability generating the disks' viscosity causing accretion itself, while the external magnetic fields could substantially modify the structure of the disk and create non-equatorial charged-particle circular orbits [61]. Motivated by specific interesting properties of the accretion disk, much research has been undertaken, including accretion disks surrounding a BH as a source of QPO in different models [62][63][64], studying the efficiency of energy release from the accretion disk [65], images of the Kaluza-Klein black hole surrounded with thin accretion disk [66] and influence of cosmic repulsion and magnetic fields on accretion disks [67].…”
Section: Introductionmentioning
confidence: 99%